A case report of small bowel perforation secondary to cytomegalovirus related immune reconstitution inflammatory syndrome in an AIDS patient. (January 2017) - Gutiérrez-Delgado, Eva María; Villanueva-Lozano, Hiram; García Rojas-Acosta, Miguel J.; Miranda-Maldonado, Ivett C.; Ramos-Jiménez, Javier
Abstract: Non-traumatic small bowel perforation is rare in adults but carries a high morbidity and mortality. The diagnosis is made on clinical suspicion, and the most common causes in developing countries are infectious diseases, being cytomegalovirus infection in immunocompromised patients the main etiology. We describe a patient with a recently diagnosed advanced stage HIV infection and an intestinal perforation associated with cytomegalovirus immune reconstitution inflammatory syndrome after highly active antiretroviral therapy initiation. Highlights: Cytomegalovirus (CMV) is the main etiology of non-traumatic perforation of the small bowel in immunocompromised individuals. We describe a case of CMV associated Immune reconstitution inflammatory syndrome. To our knowledge this is the first case of small bowel perforation due to IRIS related CMV. It is of importance for the clinician to consider CMV related IRIS as a cause of acute abdomen.